PEPTİK ÜLSERLİ OLGULARIMIZIN RETROSPEKTİF DÖKÜMÜ - ERKAN, Tülay; KUTLU, Tufan; ÇULLU, Fügen; Göksel, Süha; TÜMAY, Güngör T. (Cerrahpaşa Medical Journal, 2019)
Background and Design. This study is a retrospective report of cases with endoscopically confirmed peptic ulcer disease diagnosed at the Department of Pediatric Gastroenterology of Cerrahpaşa Medical Faculty within the past 6 years. All patients were evaluated for the use of aspirin or other nonsteroidal antiinflammatory drugs, the presence of family history and the presence of Helicobacter pylori infection. Results. Peptic ulcer was found in 41 of 1565 patients who underwent endoscopy. The mean age of the patients was 9±3.7 years (214 years), 13 being females. Thirtytwo of them were diagnosed as primary and 9 of them secondary ulcer disease. Twentytwo of the primary ulcer patients and 6 of the secondary ulcer patients were males. The majority of cases (32/41) were above 6 years of age at the time of endoscopy. Abdominal pain being prominent (59%) in primary ulcers, hematemesis and/or melena were prominent symptoms (55%) in secondary ulcers. Family, history of peptic disease was obtained in 6 cases. Seven cases had a history of aspirin usage. Sixteen cases were found to be positive for Helicobacter pylori in 22 cases detected. Thirteen of these 16 patients showed duodenal ulceration. Endoscopy revealed gastric ulcers in 15 patients, duodenal ulcers in 22 patients, esophageal + gastric ulcers in one patient, gastric + duodenal ulcers in two patients. Conclusion. Our patients, majority aged above 6 years (78%) showed male superiority, and had a predominance of primary duodenal ulcers.